PERSEPSI SISWA TERHADAP PELAKSANAAN TANGGUNGJAWAB GURU DI SMK NEGERI KOTA BUKITTINGGI - Ratna Yulianti (Universitas Negeri Padang, 2014)
Research was to obtain information about student perceptions of the implementation of the responsibilities of a teacher in terms of hence the culture, formed in accordance with the basic personality of the student countries, delivering the protégé of good citizenship, directing and guiding children, enforcing discipline for himself as well as students and others. The Total population in this study as many as 2810 people. Samples were taken by the stratified proporsional random sampling technique with a number of 94 people. Thus, it can be said that the student perceptions of the implementation of the responsibilities of a teacher on SMKN Bukittinggi needs to be improved Key words: Teacher responsibility